2020
DOI: 10.3390/cryst10121125
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis and Characterization of Sol-Gel-Derived SrTiO3-BiMnO3 Solid Solutions

Abstract: In this study, the aqueous sol-gel method was employed for the synthesis of (1−x)SrTiO3-xBiMnO3 solid solutions. Powder X-ray diffraction analysis confirmed the formation of single-phase perovskites with a cubic structure up to x = 0.3. A further increase of the BiMnO3 content led to the formation of a negligible amount of neighboring Mn3O4 impurity, along with the major perovskite phase. Infrared (FT-IR) analysis of the synthesized specimens showed gradual spectral change associated with the superposition eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…It is known that the crystal structure and magnetic properties of BiMnO 3 -based compounds can be significantly modified via chemical doping [ 7 , 8 ]. Magnetic properties of BiMnO 3 -based compounds can also be controllably changed via doping on the A- and/or B- perovskite positions [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the crystal structure and magnetic properties of BiMnO 3 -based compounds can be significantly modified via chemical doping [ 7 , 8 ]. Magnetic properties of BiMnO 3 -based compounds can also be controllably changed via doping on the A- and/or B- perovskite positions [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This demonstrated that the full substitution of Cr 3+ by Ga 3+ ions led to the formation of light blue powders, which yielded a violet blue color for the corresponding ceramic glaze. Karoblis et al [2] utilized the sol-gel method for the synthesis of (1−x)SrTiO 3 -xBiMnO 3 solid solutions in order to obtain new multiferroic material. The results indicated that single-phase perovskites with a cubic structure can only be synthesized up to x = 0.3.…”
mentioning
confidence: 99%